(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2022)
The aim of the research is to identify the level of administrative empowerment and its role in achieving administrative development in the Directorate of Education in the city of Al-Hasakah. Search for the following results: • The level of administrative empowerment for Employees in the Directorate of Education in the city of Hasaka was a medium degree, where the arithmetic average was on the total degree (2.96), according to the axes of the study as follows: In the first place was the “professional growth” axis, followed by the “communication and flow” axis in the second place Information" and "Work Teams" was at third place, "Delegating Authority" was in fourth place, and "Motivation" was at the last place. • The level of administrative development in the Directorate of Education in the city of Al-Hasakah came to a medium degree, where the arithmetic average was on the total degree (2.76). • There are no statistically significant differences at the significance level (0.05) between the mean scores of the research sample members on the questionnaire due to the gender variable. • There are statistically significant differences at the significance level (0.05) between the mean scores of the research sample members on the questionnaire due to the educational qualification variable, which is in favor of those who have a postgraduate certificate. • There are statistically significant differences at the significance level (0.05) between the mean scores of the research sample members on the questionnaire due to the variable number of years of service, which is in favor of those who have more than 10 years of service.